(untitled) (Journal of Medical & Health Sciences Review, 2025)
Combination therapy is a common approach in pharmaceutical treatments, where multiple active pharmaceutical ingredients (APIs) are combined to enhance efficacy and reduce side effects. However, analyzing these complex formulations can be challenging, especially when dealing with similar molecular structures. Raman spectroscopy offers a rapid and non-invasive solution for identifying and quantifying APIs in combination therapies. This study demonstrates the application of Raman spectroscopy for the analysis of levetiracetam, a widely used anticonvulsant, in combination with other APIs. To measure the Raman spectra of the samples a Peak Seeker Pro-Agiltron Raman spectrometer (USA) was used, equipped with laser light 785nm at 50mW power. The Raman spectral characteristics directly linked to the medicine and excipients vary as API concentrations increase. The spectral response was analyzed qualitatively and quantitatively using principal component analysis (PCA). The maximum variations in the data were explained by the first principle component (PC-1), and the next-highest source of variations is explained by each additional principal component. A total of 15 different formulations containing levetiracetam in combination with other APIs were prepared and analyzed using Raman spectroscopy. The spectra were collected using a portable Raman spectrometer, and the data was processed using principal component analysis (PCA) and partial least squares regression (PLS-R). The results showed excellent discrimination between the different formulations, with accurate identification and quantification of levetiracetam in the presence of other APIs. The advantages of Raman spectroscopy in this study include rapid analysis time (less than 5 minutes per sample), non-destructive sampling, and minimal sample preparation. The technique also offers high sensitivity and specificity, allowing for the detection of levetiracetam in complex formulations. The results demonstrate the potential of Raman spectroscopy for the analysis of APIs in combination therapies, offering a valuable tool for pharmaceutical development, quality control, and regulatory compliance.